Regulation of monocyte IL-10 synthesis by endogenous IL-1 and TNF-alpha: role of the p38 and p42/44 mitogen-activated protein kinases. - Foey, A; Parry, S; Williams, L; Feldmann, M; Foxwell, B; Brennan, F (1998)
IL-10 is an anti-inflammatory cytokine with potent immunomodulatory effects, including inhibition of cytokine production. However, regulation of monocyte IL-10 production is poorly understood. In this report we have investigated the mechanisms of LPS-induced IL-10 production by human peripheral blood monocytes and demonstrate that IL-10 synthesis is uniquely dependent on the endogenous proinflammatory cytokines IL-1 and/or TNF-alpha. LPS signal transduction in monocytes has been shown to involve activation of the p38 and p42 mitogen-activated protein kinase (MAPK) cascades. The results in this paper indicate that inhibition of p38 MAPK potently inhibited the production of IL-10, IL-1beta, and TNF-alpha, whereas blockade of the p42/44 MAPK pathway, while partially inhibiting TNF-alpha and IL-1beta production, had no effect on monocyte secretion of IL-10. Furthermore, neither the inhibition of monocyte TNF-alpha induced by IL-10 nor the stimulation of soluble TNF receptor production was affected by inhibition of the p42/44 MAPK pathway, suggesting that this signaling event is not involved in either monocyte production of or anti-inflammatory responses to IL-10. These data raise the interesting possibility that proinflammatory TNF-alpha-mediated effects may be selectively blocked without modulating the induction or the response to IL-10, whereas the signaling events associated with the anti-inflammatory events induced by IL-10 remain to be elucidated.